Preparation and characterization of photocatalyst for the conversion of co2 to methanol - Nur Sabrina, Rahmat (2015)
Due to the reliance of the world on fossil fuel as major source of energy, the CO2 emission to the environment is inevitable which is responsible for global warming. Photocatalytic reduction of CO2 to fuel, such as methanol, methane etc. is a promising way to address the CO2 emission and energy crisis. The methanol produces from the photocataytic conversion can be used as source of fuel. CdS is a classical photocatalyst shows high activity under ultraviolet (UV) light irradiation. UV light covers only 4% of the solar light spectrum, hence visible light active photocatalyst for CO2 conversion is important. In the present work, Bi2S3/CdS was synthesized as an effective visible light responsive photocatalyst for CO2 reduction. The Bi2S3/CdS photocatalyst was prepared by the hydrothermal reaction between the precursors. The prepared powder was calcined at 250 in the muffle furnace. The catalyst was characterized by X-ray diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR). The product has been analysed by using gas chromatograph flame ionization detector (GC-FID). The photocatalytic activity in methanol production as a function of time has been investigated. The maximum yield of methanol was obtained after 6 hours of reaction. The effect of CdS concentration in Bi2S3/CdS photocatalyst was investigated and the yields of methanol were increased with increasing of CdS concentration. The maximum yield of methanol was obtained with Bi2S3/CdS with 45 % of CdS. The present works shown the potentially of Bi2S3/CdS for CO2 reduction under visible light.